Global South Responses to China’s BRI Projects: A Case Study of Jakarta-Bandung High-Speed Railway Project - Prasetyo, Kanyadibya Cendana (Institute of International Studies, 2023)
China's rise as a global power in the 21st century, marked by its economic growth and political influence, has been exemplified through initiatives like the Belt and Road Initiative (BRI). The BRI has extended China's geoeconomic and geopolitical influence across Asia, Africa, Latin America, and Europe. While existing literature predominantly focuses on China's actions, this study shifts the spotlight to Global South nations' responses and strategic policies, particularly Indonesia, in the context of China's BRI projects. Drawing upon in-depth interviews, literature review, and social media analysis, this research examines how Indonesia has actively shaped the Jakarta-Bandung High-Speed Railway project within the BRI framework to pursue its objectives and interests. The study's findings highlight that the Indonesian government, in alignment with the principles of the BRI, is actively utilizing the Jakarta-Bandung High-Speed Railway project to advance its New Developmentalism approach under President Jokowi's administration. This approach embodies a narrow perspective of development by focusing on infrastructure and economic growth while ignoring political and environmental considerations. Concurrently, the project has encountered resistance from local communities, underscoring the contrasting interests between the government and the public and adding a nuanced layer to the dynamics of the BRI. This case study sheds light on the complex interplay of interests and power dynamics within the context of China's BRI projects in the Global South. It underscores the importance of considering the responses and agency of host nations and local communities in shaping the outcomes of BRI initiatives.